2017
DOI: 10.1002/nau.23194
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful trial without catheter following acute urinary retention in benign prostatic enlargement: A single centre, multivariate analysis

Abstract: Age, baseline AUA score, IPP, PV, and RV independently predict the outcome of TWOC. Patients with IPP > 9 mm, age > 65 years, baseline AUA score > 20, PV > 56 cc, or RV > 750 mL have less probability of successful TWOC in AUR and can be considered for immediate surgery following an episode of AUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
2
22
1
Order By: Relevance
“…Conversely, we found no significant differences in PSA concentrations, prostate volume, age, and residual volume between patients experiencing TWOC success and failure, in contrast with previous studies . These apparent discrepancies results could be explained by the population size and different inclusion criteria of the different studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, we found no significant differences in PSA concentrations, prostate volume, age, and residual volume between patients experiencing TWOC success and failure, in contrast with previous studies . These apparent discrepancies results could be explained by the population size and different inclusion criteria of the different studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In particular Bhomi et al found an AUC of 0.90 for an IPSS cut‐off of 16. Similarly, the American Urological Association (AUA) symptom score was recently found to be associated with TWOC success (odds ratio 1.78, 95% confidence interval 1.27–6.56; P = .038) . In accordance with these previous studies, the IPSS‐4 was shown to be predictive of TWOC success, with a significant AUC of 0.85 ( P < .001), in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The chance of successful voiding at the 1st catheter removal in this study was 46%, which corresponds to the values found in the literature, between 33% and 61% …”
Section: Discussionsupporting
confidence: 89%
“…Tiong, Sharis and Bansal et al in their respective studies demonstrated a success rate of 60%, 50% and 66.3%. [5][6][7] Average age was noted to be lesser by 3 years and 6 months in successful group in our study and was found to be a statistically significant parameter for determining success. The opinion on this association is divided in literature.…”
Section: Discussionmentioning
confidence: 77%